2012
DOI: 10.1103/physrevb.86.224417
|View full text |Cite
|
Sign up to set email alerts
|

Quantum phase transition in Heisenberg-Kitaev model

Abstract: We explore the nature of the quantum phase transition between a magnetically ordered state with collinear spin pattern and a gapless Z 2 spin liquid in the Heisenberg-Kitaev model. We construct a slave particle mean-field theory for the Heisenberg-Kitaev model in terms of complex fermionic spinons. It is shown that this theory, formulated in the appropriate basis, is capable of describing the Kitaev spin liquid as well as the transition between the gapless Z 2 spin liquid and the so-called stripy antiferromagn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
119
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 39 publications
12
119
0
3
Order By: Relevance
“…After a preliminary set of runs, we find three different phases in this quadrant: FSL, stripy, and Néel as one moves from ϕ = −90 • to 0. Noting that this matches the results from previous studies [11,12,[30][31][32], it remains to verify how our results agree with the transition points found previously. Having obtained tensors representing the phases at the two extremes of the angle window shown in Fig.…”
Section: A Fsl-stripy Transitionsupporting
confidence: 81%
See 2 more Smart Citations
“…After a preliminary set of runs, we find three different phases in this quadrant: FSL, stripy, and Néel as one moves from ϕ = −90 • to 0. Noting that this matches the results from previous studies [11,12,[30][31][32], it remains to verify how our results agree with the transition points found previously. Having obtained tensors representing the phases at the two extremes of the angle window shown in Fig.…”
Section: A Fsl-stripy Transitionsupporting
confidence: 81%
“…This value is also reported in the extended formulation on a 24-site system [12]. The restricted formulation was also studied from a slave-particle mean field approach [30] where the behavior of the order parameter itself showed a discontinuity, yet it was suggested that the transition could indeed be of either second-or weak first-order type at a value of ϕ ≈ −72 • (α ≈ 0.76), owing to the lack of quantum fluctuations beyond the mean field level in their approach. Finally, a so-called mixed PEPS approach found a phase transition at ϕ ≈ −89 • (α ≈ 0.99) [32].…”
Section: Kitaev-heisenberg Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the Kitaev spin liquid is rather stable with respect to the Heisenberg interaction 2,12,14,18 ; it remains the ground state of the KH model for a wide range of strengths of the Heisenberg interaction. Exact diagonalization studies 2,12,14 suggest a stability of the spin liquid phase for the model parameter α in the range (0.8, 1), where α is determined such that J K = 2α and J H = 1−α.…”
mentioning
confidence: 99%
“…Recently, Jackeli and Khaliullin 1 suggested that the Kitaev model could actually be realized within the honeycomb iridates with general formula A 2 IrO 3 , since the anisotropic part of the interactions among Ir-ions has the same form as the Kitaev coupling. This suggestion has triggered a lot of experimental [7][8][9][10][11] and theoretical [12][13][14][15][16][17][18] activity in the study of Na 2 IrO 3 and Li 2 IrO 3 compounds.…”
mentioning
confidence: 99%